A Communication Method between High-speed UUV and Distributed Intelligent Nodes - Ma, Xuefei; Wang, Bo; Li, Lei; Wang, Tingting; Hu, Pengpeng; Lin, Yun (Mobile networks and applications, 2020)
In this paper, a doppler distortion compensation method for underwater transmission of OFDM (Orthogonal Frequency Division Multiplexing) signals is proposed, which is used to realize real-time underwater acoustic communication between high-speed UUV (Unmanned Underwater Vehicle) and intelligent nodes. The method decomposes channel variations based on a functions with a set of known equations. OFDM symbol reconstruction is performed after the Taylor(T) FFT (Fast Fourier Transformation) process. We design an adaptive stochastic gradient descent algorithm based on MMSE criterion to learn the combiner weights for differentially coherent detection, thereby achieving adaptive channel equalization in the underwater acoustic channel. Comprehensive data and experimental data from the recent mobile acoustic communication delta are used to demonstrate the feasibility of this approach. The method can realize high-speed underwater acoustic communication, provide data sample basis for long-term big data analysis, and realize real-time communication result analysis.